THE FUNCTION OF APPLIED LINGUISTICS IN BUSINESS COMMUNICATION: BENEFITTING FROM GENRE ANALYSIS IN THE DIGITAL ERA - Nugrahaningtyas Fatma Anyassari (International Journal of Business English and Communication, 2025)
The onset of the English for Business and Professional Communication study program in vocational higher institutions in Indonesia gains more attention as the number of the study programs has increased. This study describes the teaching of applied linguistics in business communication to equip students with linguistics skills appropriate for business communication from ESP point of view and the student’s perspectives after attending the class. This study employed case study as the research method. Sampling technique used was convenient sampling by which a class of 22 second-year applied bachelor students majoring English for Business and Professional Communication participated. The methods of data collections were observation, documentation, and interview. The findings show that genre analysis being performed in two modes—as an instructional method for teachers and as an analytical method for students—raised students’ genre awareness in business communication in the digital era. The awareness helped students find how English can accommodate business and professional communication in the digital era. Some examples of worksheets and students are displayed to provide vivid illustrations. This study suggests company websites as one of authentic materials representing business communication in the digital era be used in the class to bridge the gap between students’ language skills and expected outcomes of digital business communication nowadays.